Energetic efficiency of foraging mediates bee niche partitioning. Issue 4 (17th February 2021) - Balfour, Nicholas J.; Shackleton, Kyle; Arscott, Natalie A.; Roll‐Baldwin, Kimberley; Bracuti, Anthony; Toselli, Gioelle; Ratnieks, Francis L.W.
Abstract: Revitalizing our understanding of species distributions and assembly in community ecology requires greater use of functional (physiological) approaches based on quantifiable factors such as energetics. Here, we explore niche partitioning between bumble and honey bees by comparing a measure of within‐patch foraging efficiency, the ratio of flower visitation rate (proportional to energy gain) to body mass (energy cost). This explained a remarkable 74% of the variation in the proportions of bumble to honey bees across 22 plant species and was confirmed using detailed energy calculations. Bumble bees visited flowers at a greater rate (realizing greater energy benefits) than honey bees, but were heavier (incurring greater energy costs) and predominated only on plant species where their benefit : cost ratio was higher than for honey bees. Importantly, the competition between honey bees and bumble bees had no consistent winner, thus highlighting the importance of plant diversity to the coexistence of competing bees. By contrast, tongue : corolla‐tube‐length ratio explained only 7% of the variation (non‐significant). Our results confirm the importance of energetics in understanding community ecology and bee foraging niche and highlight the energetic tightrope navigated by foraging bees, since approximately half the nectar energy gained was expended in its collection.